Sodium ion storage in Na₄MnV(PO₄)₃@C free-standing electrode - Hu, Ping (2022)
To enhance the energy density of batteries and explore intrinsic charge storage mechanism of the active materials, it is important to reduce or eliminate the use of non-active materials in electrodes, such as binder and conductive additives. Herein, free-standing Na4MnV(PO4)3@C (F-NMVP@C) fiber membrane is fabricated and directly used as a sodium-ion battery (SIB) cathode. In situ X-ray diffraction reveals that the V3+/V4+ redox reaction occurs through a solid-solution reaction while a two-phase Mn2+/Mn3+ redox reaction is identified, and both are highly reversible. Meanwhile, ex situ electrochemical impedance spectroscopy reveals that both the ion diffusion coefficient and charge transfer resistance of F-NMVP@C change reversibly during the Na+ intercalation/de-intercalation. Battery full cells are assembled based on the free-standing F-NMVP@C cathodes and F-Sb@C anodes, which manifests a high energy density (293 Wh kg−1) and good cyclability (87.5% after 100 cycles at 1 C). The high-performance free-standing cathodes and anodes shed light on the development of flexible SIBs.